Health Literacy and Social Determinants of Health Among Residents of Coal Mining Surrounding in East Kalimantan - Nurrachmawati, Annisa; Anggraeni, Ike; Permana, Lies (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Health literacy is a critical aspect of community well-being, particularly in regions affected by coal mining. The communities surrounding coal mining operations often face unique health challenges due to environmental exposures and socioeconomic factors. This emphasizes its importance of enhancing health literacy to mitigate these effects. The problem is low Health Literacy is common in developing countries. Therefore increasing health literacy is needed to support the achievement of targets related to SDGs regarding health, and other SDGs targets. Objective : This study explores the economic conditions, social determinants and health literacy Research Methods/ Implementation Methods : It was a cross-sectional study. Located in 10 villages distributed in Kutai Kertanegara district and Samarinda city. The sample was 450 people. The data collection used the HLSSF-12 questionnaire. Data analysis using Mann Whitney test Results : The results showed there was a difference in the mean Literacy score between men and women (Asymp. Sig = 0.00). There was a significant difference of mean literacy scores between middle, high and low education levels ( Asymp. Sig = 0.00) There was a significant difference of literacy scores among low and moderate family income. It was concluded that for different social determinants groups there are differences in health literacy. Conclusion/Lesson Learned : There is still a gap in health literacy, It is recommended that health literacy education begin at the family level, especially in families with low levels of education and income.